2017
DOI: 10.1007/s10461-017-1864-9
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Desires and Considerations of HIV-Positive Men in Heterosexual Relationships in New York City

Abstract: The reproductive desires of HIV-positive men have been investigated far less than those of HIV-positive women, especially in the US. This qualitative study of a sample of 94 HIV-positive men in New York City who were in a relationship with a woman of reproductive age examined their reasons for wanting a child as well as the conditions under which they would feel ready to attempt conception. Participants felt a child would make them feel normal, give meaning to their lives, or make others in their life happy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…The findings are important as supporting serodiscordant couples can be beneficial in the fight against HIV/AIDS and against HIV-related stigma. Being in a long-term relationship and feeling supported in their reproductive goals contributes to HIV-positive people’s feeling of normalcy (Hughes, 2017) and, as we found in another study, often encourages them to adhere to healthy behaviour, such as staying engaged in care and adhering to treatment (Siegel et al, 2017). Further, the possibility of serodiscordant partners to remain together and even conceive children while avoiding infection to the HIV-negative partner and the child proves that HIV is an illness that can be managed and that irrational fears of contagion—on which most HIV stigmatization are grounded—are unwarranted.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The findings are important as supporting serodiscordant couples can be beneficial in the fight against HIV/AIDS and against HIV-related stigma. Being in a long-term relationship and feeling supported in their reproductive goals contributes to HIV-positive people’s feeling of normalcy (Hughes, 2017) and, as we found in another study, often encourages them to adhere to healthy behaviour, such as staying engaged in care and adhering to treatment (Siegel et al, 2017). Further, the possibility of serodiscordant partners to remain together and even conceive children while avoiding infection to the HIV-negative partner and the child proves that HIV is an illness that can be managed and that irrational fears of contagion—on which most HIV stigmatization are grounded—are unwarranted.…”
Section: Discussionmentioning
confidence: 86%
“…Both members of each couple completed the study separately but at the same time. Recruitment, eligibility criteria, and data collection procedures were described in greater detail in another publication (Siegel, Meunier, Tocco, & Lekas, 2017). All study procedures were approved by the Institutional Review Board at Columbia University Medical Center and informed consent was obtained from all study participants.…”
Section: Methodsmentioning
confidence: 99%
“…Men living with HIV who wanted to conceive with a serodiscordant female partner were historically advised to undergo a procedure known as sperm washing, separating spermatozoa (which do not carry HIV) from seminal fluid and associated non-sperm cells (Nicopoullos et al 2010). However, using this method is expensive, few fertility clinics offer it and many couples have been reluctant to use it as they prefer to conceive 'naturally' (Kelly et al 2011, Siegel et al 2018. As TasP has become accepted practice, and especially in light of evidence supporting U = U, clinicians have increasingly endorsed natural conception (Barber et al 2019).…”
Section: Hiv Sexualit Y and Reproductionmentioning
confidence: 99%
“…It is unclear, however, if this is because of researchers' explicit focus on gay men's sex lives or because having children is unimportant to HIV-positive gay men. While it is likely that few of them decide to become parents, limited evidence suggests that, similar to heterosexual men living with HIV (Rodriguez et al 2017, Siegel et al 2018, Weber et al 2017, it is not uncommon for HIV-positive gay men to want or plan to have children. In a quantitative study conducted at a London HIV clinic, Sherr (2010) found that approximately one third of men who have sex with men 'had considered having children' (5).…”
Section: Hiv Sexualit Y and Reproductionmentioning
confidence: 99%
“…In sub-Saharan Africa, up to 60% of new infections occur in stable, HIV-serodifferent partnerships, in which both partners often place great value on having children [1][2][3][4][5][6][7]. HIV-uninfected women who conceive with a partner living with HIV face HIV acquisition and perinatal transmission risks, highlighting the importance of periconception counseling for men living with HIV (MLWH) to prevent transmission [8][9][10][11][12]. Antiretroviral treatment (ART), pre-exposure prophylaxis (PrEP), limiting condomless sex to peak fertility, and sperm processing are effective HIV prevention strategies for HIV-serodifferent couples wherein the male partner is living with HIV and they want to have a child [13].…”
Section: Introductionmentioning
confidence: 99%